Health Literacy and Awareness of Atrial Fibrillation. Issue 4 (April 2017) - Reading, Stephanie R.; Go, Alan S.; Fang, Margaret C.; Singer, Daniel E.; Liu, In‐Lu Amy; Black, Mary Helen; Udaltsova, Natalia; Reynolds, Kristi; ,
Abstract : Background: Atrial fibrillation (AF) is the most common clinically significant arrhythmia in adults and a major risk factor for ischemic stroke. Nonetheless, previous research suggests that many individuals diagnosed with AF lack awareness about their diagnosis and inadequate health literacy may be an important contributing factor to this finding. Methods and Results: We examined the association between health literacy and awareness of an AF diagnosis in a large, ethnically diverse cohort of Kaiser Permanente Northern and Southern California adults diagnosed with AF between January 1, 2006 and June 30, 2009. Using self‐reported questionnaire data completed between May 1, 2010 and September 30, 2010, awareness of an AF diagnosis was evaluated using the question "Have you ever been told by a doctor or other health professional that you have a heart rhythm problem called atrial fibrillation or atrial flutter?" and health literacy was assessed using a validated 3‐item instrument examining problems because of reading, understanding, and filling out medical forms. Of the 12 517 patients diagnosed with AF, 14.5% were not aware of their AF diagnosis and 20.4% had inadequate health literacy. Patients with inadequate health literacy were less likely to be aware of their AF diagnosis compared with patients with adequate health literacy (prevalence ratio=0.96; 95% CI [0.94, 0.98]), adjusting for sociodemographics, health behaviors, and clinical characteristics. Conclusions: Lower health literacy is independently associated with less awareness of AF diagnosis. Strategies designed to increase patient awareness of AF and its complications are warranted among individuals with limited health literacy.